Neighborhood environment and walking for transport and recreation in Central European older adults - Jana Pelclová; Karel Frömel; Ladislav Bláha; Izabela Zając‐Gawlak; Lenka Tlučáková (Palacky University, 2012)
BACKGROUND: Neighborhood environment is an aspect that influences physical activity, mainly walking. Hence, built environment research may help to use environmental and policy strategies to increase physical activity. OBJECTIVE: This cross-sectional study aimed to investigate the association between perceived neighborhood environment and meeting the recommendation of at least 30 minutes of walking 5 or more days a week within active transportation and leisure-time domains in Central European older adults. METHODS: Four hundred and fifty six healthy ambulatory older adults filled out the modified and culturally adapted version of the Neighborhood Environment Walkability Scale (ANEWS) for obtaining perceived environment information and the self-administrative long version of the International Physical Activity Questionnaire (IPAQ) for assessing physical activity levels. RESULTS: Respondents living in high residential density neighborhoods (OR 1.87), living in flats (OR 2.09) and in location with ≤100,000 inhabitants (OR 1.63) were more likely to meet recommendation within walking for transportation. Owning a dog was associated with meeting recommendation within walking for leisure (OR 1.69). CONCLUSIONS: This study supported the specific impact of environment on meeting PA recommendations within transportation and leisure time walking in older adults. Out of all perceived neighborhood environmental attributes received from ANEWS questionnaire, only high residential density was positively associated with meeting recommendation within total walking and walking for transport.